(untitled) (Swiss Medical Weekly, 2017)
Antimicrobial stewardship (AMS) is an important component in the fight against antimicrobial resistance. Currently, few hospitals have an ongoing institutional AMS programme. Swissnoso – the national centre for infection prevention – has launched a national Swiss AMS initiative supported by the office of public health. To guide AMS priorities and resources, current AMS activities in Switzerland were assessed. We distributed an internet-based questionnaire directed mainly to board-certified infectious diseases specialists and, if not available, senior internal medicine staff. Responses were received from 63/134 hospitals surveyed. More than 90% were in favour of national treatment guidelines currently in development under the umbrella of the Swiss society for infectious diseases. Many AMS activities – such as antimicrobial formulary restrictions and approval systems, review of antimicrobial prescriptions with point of care intervention, and direct feedback or therapeutic drug monitoring – are currently lacking in the majority of Swiss hospitals surveyed. Development of a modular formal AMS standard for Swiss hospitals may aid in advancing current AMS strategies and in introducing AMS programmes in Switzerland. In combination with the surveillance of antimicrobial use and resistance by ANRESIS, the national antimicrobial resistance surveillance system, this approach may reduce the use of antimicrobial agents and consequently the risk of emergence of multi-resistant pathogens.